Training research as a cross-cutting axis in teacher training - Burga Gutérrez, Rosa María (2022)
Formative research in recent decades is positioned in the professional training curricula of the various areas of knowledge. Teacher training has not been the exception. Formative research has been included as a transversal axis of the curriculum, with the purpose of developing investigative skills and promoting the development of higher-order thought processes. For this, it has been necessary to manage changes in didactics, in evaluation and above all to have a teacher trainer who has the necessary qualities to accompany the student to build knowledge autonomously and in the future be capable of transforming their reality. Therefore, formative research in teacher training should focus on: a) preparing future professionals to make innovative use of existing scientific and technological knowledge and empower them to take on the challenge of transforming the educational reality from research; and b) Develop a positive and ethical attitude, evidenced in the practice of a scientific culture manifested in scientific thinking and acting.